Combat against antibiotic resistance is a challenge in Bangladesh - Roney, Miah; Moyeenul Huq, A. K. M.; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier, 2024)
To the Editor, Antibiotics are a class of drug used to treat or prevent infections caused by bacteria; they function by either eradicating the organism or stopping its growth. Penicillin, cephalosporins, macrolides, fluoroquinolones, and urinary anti-infectives are examples of common antibiotics. To effectively treat the illness, it's critical to take antibiotics as directed by a physician and to finish the entire course of treatment. Antibiotic resistance is a serious issue in Bangladesh as a result of subpar healthcare practices, antibiotic abuse, and overuse. Antibiotic resistance is the result of bacteria changing and becoming resistant to an antibiotic's effects. Moreover, one of Bangladesh's biggest challenges is the fight against antibiotic resistance. Therefore, the purpose of this letter is to raise awareness of the antibiotic resistance in Bangladesh.